Padanan Kosakata Indonesia ke Arab Dalam Bidang Sejarah - khotami, muhamad; Mubarak, Muhammad Zacky; Suparno, Darsita (IAIN Bone, 2024)
The purpose of this study is to explain how translation techniques are used to translate terms, especially prehistoric terms, and to explain the process of mapping terms referring to several dictionaries. The method used in this research is descriptive qualitative research. This research found 206 data of prehistoric terms from the book Atlas of Indonesian Prehistory and other data sources. The techniques is used for data collection, namely listening and reading. Several translation techniques are used to translate the terms: Kalke translation method totaling 59 data, description translation method totaling 33 data, amplification translation method totaling 16 data, reduction translation method totaling 1 data, borrowing translation technique totaling 71 data, and general equivalent technique totaling 26 data. Furthermore, several terms were analyzed using the word matching process and grouped based on their respective matching processes. 128 data were obtained using the translation process, 48 data using the absorption process, and 30 data using a combination of translation and absorption. The results show that the terms can be translated from one language to another and analyzed using various translation techniques and the process of matching the translated terms.Tujuan studi ini untuk mengungkap teknik penerjemahan istilah prasejarah, dan menjelaskan proses pemadanan istilah tersebut dari beberapa kamus. Metode yang digunakan dalam penelitian ini adalah penelitian deskriptif kualitatif. Penelitian ini menemukan sebanyak 206 data istilah prasejarah dari buku Atlas Prasejarah Indonesia dan sumber data lainnya. Teknik yang digunakan untuk pengumpulan data adalah teknik simak dan baca. Beberapa teknik penerjemahan digunakan untuk menerjemahkan istilah: Metode penerjemahan kalke berjumlah 59 data, metode penerjemahan deskripsi berjumlah 33 data, metode penerjemahan amplifikasi berjumlah 16 data, metode penerjemahan reduksi berjumlah 1 data, teknik penerjemahan peminjaman berjumlah 71 data, dan teknik padanan umum berjumlah 26 data. Kemudian istilah-istilah tersebut dianalisis menggunakan proses pemadanan kata dan dikelompokkan berdasarkan proses pemadanannya masing-masing. Didapatkan 128 data menggunakan proses penerjemahan, 48 data menggunakan proses penyerapan, dan 30 data menggunakan kombinasi penerjemahan dan penyerapan. Hasilnya menunjukkan bahwa istilah-istilah dapat diterjemahkan dari satu bahasa ke bahasa lain dan dianalisis menggunakan berbagai teknik penerjemahan dan proses pemadanan istilah-istilah yang diterjemahkan.